Incentive Contracts and Performance Measurement - Baker, George P. (Journal of Political Economy, 1992)
This paper examines the characteristics of incentive contracts in which the agent's payoff is not based on the principal's objective. The author shows that contracts based on such performance measures will not, in general, provide first-best incentives, even when the agent is risk neutral. The form of the optimal contract and the efficiency of this contract depend on the relationship between the performance measure used and the principal's objective. The model provides a simple and intuitive statistical measure. Applications to various incentive contracting situations, including the "gaming" of performance measures, the use of revenue-based sales commissions, and relative performance evaluation, are presented. Copyright 1992 by University of Chicago Press.